METHODOLOGICAL AND APPLIED ASPECTS OF MANAGEMENT OF RISKS OF ACCIDENTS IN PRODUCTION - BLAZHYNSKA, Tetiana (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article analyzes the issues of ensuring the stable operation of enterprises and organizations by eliminating and preventing the risks of accidents at work. Effective risk management in this area allows ensuring the intellectual and personnel safety of the enterprise. In addition, the leveling of risks and threats in the field of occupational safety is also the stability of the business entity, which at the same time affects its labor productivity. That is why the purpose of the study was defined as the generalization and further development of methodological and applied aspects of occupational accident risk management. It is argued that improving the level of industrial safety requires a transformation of traditional approaches to occupational safety management, in particular, a transition from a reactive model to a risk-oriented one. This approach involves systematic identification, analytical processing and multi-level assessment of occupational risks in order to develop effective preventive measures. In this context, it is advisable to implement the concept of dynamic risk-based insurance, which takes into account the variability of the risk level over time and ensures the adaptability of financing mechanisms based on digital analysis of production factors. Key management actions have been identified, which are structured according to the level of risk of business entities. A number of methods within the risk-oriented model for the management of industrial injuries have been analyzed, namely engineering, expert, social and model. A classification of occupational risk categories has been developed based on an integrated assessment of the main factors. A system for forming a financial mechanism in the field of labor protection is proposed, which ensures the integration of economic motivation of employers with the tasks of increasing the level of safety in the workplace. Its conceptual advantage is the combination of incentive and regulatory instruments that operate on the principles of transparency, targeting and adaptability to changes in the production environment.
Keywords: enterprise management; personnel management; risks and threats; risk management; leveling; production process; accidents